1993
DOI: 10.11606/issn.2594-5904.rpef.1993.138750
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a competitive triathlon on plasma concentrations of tryptophan and branched-chain amino acids

Abstract: The aim of this work was to determine the acute responses of tryptophan and branched chain amino acids to a triathlon competition. Fourteen male triathletes were studied. All took part in a international triathlon race consisting of 1,5 km swimming, 40 km biking and 10 km running. Venous blood samples were drawn before (-24 h) and after (15 min) the triathlon. Plasma concentration of branched chain amino acids and total and free tryptophan were determined. Branched chain amino acids decreased from 463 -108.3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Morales found through research that branched chain amino acids can increase the rate of protein synthesis and metabolism in athletes, thereby increasing the athlete's physiological response and keeping the mental state in a good state [7]. In order to study the effect of supplementing branched chain amino acids on certain hormone responses of athletes, Osorio used modern instruments and immune tracking methods to conduct research from the molecular level, and found that branched chain amino acids can increase growth hormone in athletes, which can be greatly improved, alleviate sports fatigue of athletes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Morales found through research that branched chain amino acids can increase the rate of protein synthesis and metabolism in athletes, thereby increasing the athlete's physiological response and keeping the mental state in a good state [7]. In order to study the effect of supplementing branched chain amino acids on certain hormone responses of athletes, Osorio used modern instruments and immune tracking methods to conduct research from the molecular level, and found that branched chain amino acids can increase growth hormone in athletes, which can be greatly improved, alleviate sports fatigue of athletes [8].…”
Section: Introductionmentioning
confidence: 99%